Cover Image. (23rd July 2019) - Bi, Hongyan; Zhong, Chunyi; Shao, Mingke; Wang, Chengyu; Yi, Jia; Qiao, Liang; Zhang, Junbo
Abstract : The cover image is based on the Research Article Differentiation and Authentication of Fishes at Species Level Through Analysis of Fish Skin by MALDI TOF MS by Hongyan Bi et al., https://doi.org/10.1002/rcm.8474 .